PENGEMBANGAN BAHAN AJAR BERBASIS GOOGLE SITE PADA MATERI SISTEM PEREDARAN DARAH - Dhevita Septia Sari; Anak Agung Oka; HRA Mulyani (EDUBIOLOCK, 2026)
The aim pursued through this creation lies in generating a viable instructional medium anchored on Google Site, while simultaneously positioning it as an alternative resource that reinforces present-day learning practices through the employment of digital tools. The framework adopted for this creation is ADDIE (Analysis, Design, Development, Implementation, Evaluation). The sequence of creation involved verification of the product by subject specialists, layout specialists, and limited student trials. The findings revealed that the Google Site-oriented instructional medium attained an approval rate of 95% from subject specialists and 97.5% from layout specialists, both of which are classified under the “Highly Applicable” standard. Trials with learners likewise indicated highly favorable feedback, yielding 82%, which is also grouped within the “Highly Applicable” level. Learners’ feedback predominantly highlighted that this instructional medium was engaging, user-friendly, and facilitated comprehension. Accordingly, it may be inferred that this Google Site-based instructional medium is extremely proper to be employed as a forward-looking resource that strengthens the ongoing technology-driven learning process.